DISSOLVED CLOUDS: ERICSSON’S VAUDREUIL DATA CENTRE AND INFRASTRUCTURAL ABANDONMENT - Velkova, Julia; Brodie, Patrick (AoIR Selected Papers of Internet Research, 2020)
The past decade has seen the accelerated growth and expansion of large-scale data centre operations across the world to support emerging consumer and business data and computation needs. These buildings, as infrastructures responsive to changing global economic and technological terrain, are increasingly modular, and must be built out rapidly. However, these conditions also mean that their paths to obsolescence are shortened, their lifespans dependent on shifting corporate strategies and advances in consumer technology. This paper theorises and empirically explores material, infrastructural abandonment that emerges in this process of data centre construction across different geographical contexts. To do so, we analyse the socio-material construction of an international network of large-scale data centres by global telecom giant Ericsson, and the abrupt abandonment and suspension of one of its nodes in Vaudreuil, Québec in 2017 after only nine months of operation. Employing autoethnography, site visits, and qualitative interviews with data centre architects and staff in Sweden and Canada, we argue that the ruins of abandoned ’cloud’ infrastructure represent the disjunction between the ’promise’ of digital infrastructure for local communities and the market interests of digital companies. With its focus, the paper takes ruination and discard as perspectives through which to understand the complexity of emergent datafied futures and the socio-technical reshaping of internet infrastructures.